2014
DOI: 10.1128/iai.02158-14
|View full text |Cite|
|
Sign up to set email alerts
|

Endotoxin-Induced Endothelial Fibrosis Is Dependent on Expression of Transforming Growth Factors β1 and β2

Abstract: f During endotoxemia-induced inflammatory disease, bacterial endotoxins circulate in the bloodstream and interact with endothelial cells (ECs), inducing dysfunction of the ECs. We previously reported that endotoxins induce the conversion of ECs into activated fibroblasts. Through endotoxin-induced endothelial fibrosis, ECs change their morphology and their protein expression pattern, thereby suppressing endothelial markers and upregulating fibrotic proteins. The most commonly used fibrotic inducers are transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 34 publications
5
21
0
Order By: Relevance
“…These findings are in agreement with the data presented here, as endothelial cells transfected with siRNA-TRPM4 adopt a fibrotic-like phenotype in addition to acquiring several fibrotic markers and losing endothelial proteins. TRPM4 downregulation induces a change in the protein expression pattern of endothelial cells that promotes fibrotic-like protein expression similar to that previously reported in nontransfected wild-type endothelial cells exposed to TGF-b1 and TGF-b2 [8,9,49,50]. We observed that endothelial cells express and secrete both of these TGF-b isoforms when TRPM4 expression was suppressed.…”
Section: Transient Receptor Potential Melastatin 4 Participates In Casupporting
confidence: 78%
“…These findings are in agreement with the data presented here, as endothelial cells transfected with siRNA-TRPM4 adopt a fibrotic-like phenotype in addition to acquiring several fibrotic markers and losing endothelial proteins. TRPM4 downregulation induces a change in the protein expression pattern of endothelial cells that promotes fibrotic-like protein expression similar to that previously reported in nontransfected wild-type endothelial cells exposed to TGF-b1 and TGF-b2 [8,9,49,50]. We observed that endothelial cells express and secrete both of these TGF-b isoforms when TRPM4 expression was suppressed.…”
Section: Transient Receptor Potential Melastatin 4 Participates In Casupporting
confidence: 78%
“…Future experiments must focus on evaluating the effect of Ang-(1-7) on oxidative stress in muscle wasting induced by LPS and evaluating the possible antioxidant role of this peptide in this model. LPS has been reported to induce the expression of TGF-β1 (transforming growth factor β1) in endothelial cells [74][75][76]. Furthermore, TGF-β1 is capable of inducing skeletal muscle atrophy [77] through UPP activation and the up-regulation of atrogin-1 and MuRF-1 [78].…”
Section: Discussionmentioning
confidence: 98%
“…We defined the PVECs that underwent EndMT (EndMTPVECs) as those showing double labeling with antibodies against CD31 and ␣-SMA, or with antibodies against CD31 and S100A4 (15)(16)(17). Changes in the number of EndMTPVECs after LPS challenge are shown in Fig.…”
Section: Pulmonary Vascular Endmt Increased During Pvecs Injury In Vivomentioning
confidence: 99%
“…Growing evidence suggests that EndMT is enhanced or triggered by various factors including transforming growth factor-␤ (TGF-␤), hepatocyte growth factor, fibroblast growth factor, and so on. TGF-␤ is likely to be the most potent among factors that induce EndMT (17,19,28).…”
mentioning
confidence: 99%